Adoption of Online Grocery Shopping: Personal or Household Characteristics?. Issue 3 (3rd July 2017) - Van Droogenbroeck, Ellen; Van Hove, Leo
ABSTRACT: This article analyzes how sociodemographic characteristics impact the adoption of online grocery shopping, and relies on the Motivation-Opportunity-Ability (MOA) model to explore what these sociodemographics actually capture and how they are linked with consumer motivations. The researchers exploit a survey among 468 customers of Belgian supermarket chain Colruyt. Their logistic regression shows that while variables at the personal level do affect adoption of the online channel, consumers' motivations to adopt in fact lie on the household level. In particular, the effect of age disappears or becomes less strong when it is combined with household characteristics. An examination of respondents' self-reported motivations confirms that age does not only capture a person's ability to use the technology but also its usefulness for that person's household, in that age is correlated with the presence of young children and the working situation in the household.